ANALISIS FAKTOR PENYEBAB PERGESERAN ADAT PERKAWINAN MINANGKABAU DI NAGARI LUBUK BASUNG KABUPATEN AGAM SUMATERA BARAT - Elsa Fitria; Ahmad Eddison; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by the traditional marriage culture of the people in Nagari Lubuk Basung which is starting to experience a shift. Based on the background and symptoms of the problems that the author has described, the problems that arise are what are the factors causing the shift in the Minangkabau marriage custom in Nagari Lubuk Basung, Agam Regency, West Sumatra? The purpose of this study was to analyze the factors causing the shifting of marriage customs in Lubuk Basung Nagari. In this research the writer will present the data is the result of research conducted by the author at the research location namely in Jorong IV Surabayo Nagari Lubuk Basung, where this research uses observation data collection techniques, interviews, and questionnaires. In this study, the population numbered 1563 households, the authors took a sample of 10% of the 1,563 population. Thus the number of samples in this study were 156 households as respondents for filling out the author's research questionnaire. The results of this study were analyzed using quantitative descriptive analysis techniques. Quantitative descriptive analysis was conducted to obtain an overview of the respondents' answers to the research variables used. Based on the results of the research conducted, the factors that caused a shift in the Minangkabau marriage customs in Nagari Lubuk Basung were factors from outside the community as evidenced by the results of the calculation of respondents who answered